The Politics of Appropriations Earmarks: Who Gets What and Why - Garcia, Sandy; Laurie, Keely (CSUCI Journal of Undergraduate Research, 2013)
Earmarks. Few things in contemporary politics are as universally denounced and so miserably misunderstood. An appropriations bill allocates specific funds for an identifiable project or program in the state or district of a member of Congress. The U.S. Constitution invests Congress with the “power of the purse,” the power to spend money1. Scott Frisch and Sean Kelly argue that earmarks are a means for individual representatives to get government spending to reflect the interests of their constituents.